Pendidikan Pancasila bagi Penguatan Kebangsaan terhadap Dampak Globalisasi - Mulyatno, Ahmad Dwi; Triwinarso, Arif; Nugroho, Taufik (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2023)
Pancasila is an important provision for the Indonesian nation in facing the effects of globalization. Pancasila in general can be accepted by all parties, especially the Indonesian nation which is plural, diverse, and can absorb new values that exist in society and can be beneficial for the survival of the nation's generation, especially the Special Region of Yogyakarta. and can be applied in everyday life. The values of Pancasila are the noble values of the Indonesian people. Through literature research, this study aims to identify and the importance of Pancasila Education. In conclusion, it needs regulatory strengthening from the government and consistency of teachers in Pancasila Education.